"Being one, but not being the same": A dyadic comparative analysis on ethnic socialization in transcultural foster families in the Netherlands. Issue 2 (8th July 2021) - Degener, Clementine J.; van Bergen, Diana D.; Grietens, Hans W. E.
Abstract: To gain insight into ethnic socialization by ethnic majority foster parents who take care of ethnic minority foster youth, we conducted a comparative dyadic analysis, based on 16 foster parent‐foster youth dyads. Outcomes show that foster parents' first concern was providing a safe environment for their foster youth, and not ethnic minority socialization. Foster parents seem to strive to belong together as one family with their foster youth. As part of those efforts, they would incorporate ethnicity differences, and/or struggles with how to address them. This occurred in a reciprocal socialization process with their foster youth. Next, although foster youth could experience discrimination, there seems to exist a relative silence about this issue in foster families. Results furthermore show that birth parents may play a role as connectors with the ethnic backgrounds of the foster youth. Foster parents may need guidance by foster care agencies in learning how to address ethnicity issues openly, teaching their foster youth how to survive in a society where ethnic minority discrimination occurs, and involving birth parents in the ethnic socialization of the youth.